TINJAUAN YURIDIS TERHADAP KORBAN PENIPUAN OLEH WARGA NEGARA ASING BERDASARKAN PUTUSAN PIDANA NOMOR 129/PIDSUS/2020/PN Btm - AISYA VIJAYASHREE; R. Rahaditya (Jurnal Hukum Adigama, 2022)
Legal protection for witnesses and victims of crime has many weaknesses, among themost basic weaknesses is the neglect of the rights of crime victims in the process of handlingcriminal cases. From the case of Foreign Citizens China came to Indonesia using a residencepermit Free Visit Visa for 30 (thirty) days for tourist purposes, committing online fraud throughthe QQ application, SKYPE and a sum of money to be transferred to the defendant’s account.Thedefendant has been indicted by the Public Prosecutor with a single charge as regulated in Article122 letter a of the Law of the Republic of Indonesia Number 6 of 2011 concerning Immigration.The judge decided that the defendant was sentenced to Article 122 letter a of the Law of theRepublic of Indonesia Number 6 of 2011 concerning Immigration and Law Number 8 of 1981concerning the Law of Criminal Procedure. That the victim did not receive a protection decisionfor fraud committed by the accused Foreign Citizen and the sentence for the defendant was not inaccordance with what it should have been.Fraud is a criminal activity carried out for profit, fraudcommitted online should be subject to Law Number 19 of 2016 concerning Amendments of LawNumber 11 of 2008 concerning Information and Electronic Transactions. Law Number 13 of 2006and Victims are described in Article 1 number 2 of Law Number 13 of 2006, concerning theProtection of Witnesses and Victims.